Multi-functional pH-sensitive active and intelligent packaging based on highly cross-linked zein for the monitoring of pork freshness. (15th March 2023) - Kong, Jianglong; Ge, Xiaohan; Sun, Yuting; Mao, Meiru; Yu, Hongrui; Chu, Runxuan; Wang, Yi
Graphical abstract: Highlights: An intelligent packaging film with antimicrobial and antioxidant effects was formed. Mesoporous silica nanoparticles loaded with tea tree essential oil were added. Blueberry extract was added as a colorimetric pH indicator. The film can easily and precisely monitor the storage time of meat by a mobile phone. Abstract: Intelligent packaging not only protects food from environmental hazards but intuitively monitors the changes of food quality and safety. A novel intelligent packaging film with pH sensitivity and antibacterial and antioxidant effects was developed based on the highly cross-linked zein. The composite film with 0.05 g/g crosslinking agent had the best mechanical properties. The tensile strength (TS) and elongation-at-break (EBA) were 2.42 and 1.53 times of that of zein film, respectively. Moreover, the intelligent packaging showed longstanding antimicrobial and antioxidant effects because of the addition of the tea tree essential oil (TTEO)-loaded mesoporous silica nanoparticles (MSNs). The blueberry anthocyanin as colorimetric indicator was added in the packaging film to monitor the safety of meat products using a mobile phone. The color of the composite film as the packaging of the pork products changed from colorless to brown after 9-day storage to show the spoilage of the pork. To the best of our knowledge, this is the first-time report of 1) the application of TTEO-loaded MSNs for food packing, 2) the addition of TTEO as the antimicrobial agent for zein film, and 3) using the applications of mobile phone to measure the RBG value of the zein-based film. This study offers an example of the highly promising biodegradable intelligent packaging with multi-functions for the enhancement of food safety.